THE DIALECTAL COMPARISON BETWEEN MANINJAU AND TIKU SUBDIALECT: LEXICAL VARIATION - Nurvemi Sultana; Havid Ardi (Universitas Negeri Padang, 2019)
Lexical variation is the different use of lexicon as a linguistic element in particular language. There have been many researchers who conducted an analysis of lexical variation in dialects of minangkabau language. However, there is no study about lexical variation which analyze the lexical variation in Maninjau and Tiku subdialect. Thus, this research aimed to analyse the lexical variation in Maninjau and Tiku subdialect. The data is 200 words taken from swadesh list and 34 other basci words. The data is collected from the native spaker from different villages or kanagarian in these two area. This study aims to find out the lexical similarities and lexical differences. Furthermore, it used a simple calculation of dialectometric technique to determine the percentage of dialect differences. This research is a descriptive study with qualitative approach. The result of the findings shows the number of lexical similarities is higher than the lexical differences. It is found the 152 similar lexicons and 82 different lexicons. From the calculation of dialectometric technique, it is found the percentage of lexical differences 34%